Mycogenic sensitization as a risk factor for cardiovascular complications in arterial hypertension - Кравчун, Павло Григорович; Дєлєвська, Валентина Юріївна; Dielievska, Valentyna; Kravchun, Pavlo H. (My University, 2018)
The aim of the work was to study the prevalence of mycogenic sensitization in arterial hypertension (AH) and its relationship with the disease severity, progression of chronic heart failure (CHF) and contractilic function of myocardium. 44 patients with II and III stages of AH and II - III functional classes of CHF by NYHA (mean age 62.3 ± 1.7 years, 24 males and 20 females) were examined for the presence of mycogenic sensitization. The levels of serum specific IgE antibodies (sIgE) were measured to Candida maltosa, Saccharomyces cerevicae, Candida albicans, Candida crusei, Aspergillus fumigatus, Aspergillus flavus, Aspergillus niger, Penicillium chrysogenum, Penicillium tardum, Penicillium expansum, Alternaria tenuis, Trichophyton rubrum, Fusarium oxysporum, Cladosporium herbarum, Rhizopus nigricans, Mucor pusillus by an ELISA. The presence of mycogenic sensitization was determined at the level of sIgE > 50 KU/l.